Hydrophilic interaction chromatography a guide for practitioners - Olsen, Bernard A., 1953-; Pack, Brian W., 1970- (Hoboken, N.J. : John Wiley & Sons, Inc., 2013)
"This book provides background information, guidance for method development, and a discussion of applications in the field of hydrophilic interaction chromatography (HILIC.) The book serves as a valuable reference tool for scientists confronted with an analysis problem involving polar compounds to determine if HILIC would be a good choice to pursue and helps them in choosing initial experimental conditions. The book gives a detailed description of the HILIC retention mechanisms and specific information regarding application areas spanning a wide range of industries.Topics include: HILIC retention mechanisms, Stationary Phases for HILIC, HILIC Method Development, Pharmaceutical and Other Applications of HILIC, HILIC for Drug Discovery, HILIC in Two-Dimensional Separations"--
Machine generated contents note: Chapter 1. Separation Mechanisms in Hydrophilic Interaction Chromatography 1.1 Introduction 1.2 Historical Background. Recognition of the contribution of partition, ion exchange and reversed-phase interactions to the retention process 1.3 Recent studies on the contributory mechanisms to HILIC retention 1.3.1 Overview 1.3.2 Contribution of adsorption and partition to HILIC separations 1.3.3 Further studies on the contribution of ionic retention in HILIC 1.3.3.1 Introduction 1.3.3.2 Mobile phase considerations for the separation of ionogenic compounds 1.3.3.3. Ionisation state of the column as a function of pH 1.3.3.4 Quantitation of ionic retention effects on different columns 1.3.4 Reversed-phase retention on bare silica 1.3.5 Electrostatic Repulsion Hydrophilic Interaction Chromatography (ERLIC)- a new separation mode in HILIC. 1.4 Conclusions Chapter 2. Stationary Phases for HILIC 2.1 Introduction 2.2 HILIC stationary phases 2.2.1 Underivatized silica 2.2.1.1 Totally porous silica particles 2.2.1.2 Superficially porous (core shell) silica particles 2.2.1.3 Monolithic silica 2.2.1.4 Ethylene Bridged Hybrids (BEH) 2.2.2 Derivatized silica 2.2.2.1 Neutral derivatized silica 2.2.2.2 Zwitterionic derivatized silica 2.2.2.3 Positively charged derivatized silica 2.2.2.4 Negatively charged derivatized silica 2.2.3 Non-silica phases 2.2.3.1 Amino phases 2.2.3.2 Sulfonated S-DVB phases 2.3 Commercial HILIC phases 2.3.1 Efficiency comparison 2.3.2 Retention and selectivity comparisons 2.4 Conclusions Chapter 3. HILIC Method Development 3.1 Introduction 3.2 General method development considerations 3.2.1 Method objectives 3.2.2 Sample consideration 3.2.3 Systematic method development 3.3 Method development strategies 3.3.1 Systematic approach to column screening 3.3.2 Optimization of method parameters 3.3.2.1 Final column selection 3.3.2.2 Organic solvents 3.3.2.3 Mobile phase pH 3.3.2.4 Buffer types and concentration 3.3.2.5 Column temperature 3.3.2.6 Sample solvents 3.4 Detection for HILIC methods 3.4.1 Mass Spectrometry detector (MS) 3.4.2 Charged aerosol detector (CAD) 3.5 Conclusions Chapter 4. Pharmaceutical Applications of Hydrophilic Interaction Chromatography 4.1 Introduction 4.1.1 Definition of the problem 4.1.2 Selection of conditions 4.1.3 Validation of the method 4.1.4 General references 4.2 Determination of Counterions 4.2.1 Salt selection and options for counterion determination 4.2.2 Specific counterion analysis 4.2.3 Counterion screening with gradient elution 4.2.4 Suitable reference standards for counterion analysis 4.3 Main Component Methods 4.3.1 Potency/assay methods 4.3.2 Equipment cleaning verification assays 4.3.3 Dissolution methods 4.4 Determination of Impurities 4.4.1 Impurity screening and orthogonal separations 4.4.2 Impurity identification 4.4.3 Specific impurity determination 4.4.3.1 Pyrimidines, purines, nucleosides 4.4.3.2 Hydrazines with ethanol as weak solvent 4.4.3.3 Neutral and charged polar impurities in a drug substance 4.4.3.4 Polar basic compounds and impurities 4.4.4 Statistical design of experiments (DOE) for optimization 4.5 Excipients 4.5.1 Parenteral and solution formulations 4.5.2 Tablets, capsules and inhalation products 4.5.3 Sugars 4.5.4 Stabilizers and antioxidants 4.6 Chiral Applications 4.6.1 Chiral selectors and HILIC 4.6.1.1 Cyclodextrins 4.6.1.2 Macrocyclic antibiotics 4.6.1.3 Chiral crown ethers 4.6.1.4 Cyclofructans 4.6.2 Conclusions for chiral separations 4.7 Conclusions Chapter 5. Hydrophilic Interaction Chromatography (HILIC) for Drug Discovery 5.1 Drug Discovery Model 5.2 HILIC Applications for in vitro Biology 5.2.1 Biological screening and hit finding 5.2.1.1 Target selection and assay validation 5.2.1.2 High-throughput screening 5.2.2 New drug discovery strategies 5.3 HILIC Applications and Advances for Discovery Chemistry 5.3.1 Lead identification 5.3.2 Lead optimization 5.3.2.1 ADME profile 5.3.2.2 Biopharmaceutics 5.3.2.3 Chiral purity 5.3.3 Candidate selection 5.4 Practical Considerations 5.5 Conclusions Chapter 6. Advances in Hydrophilic Interaction Chromatography (HILIC) for Biochemical Applications 6.1 Introduction 6.2 Carbohydrates 6.2.1 Mono- and disaccharides 6.2.2 Oligosaccharides and polysaccharides 6.2.3 Glycans 6.2.3.1 Glycan and glycopeptide analysis 6.2.3.2 HILIC for sample enrichment 6.3 Nucleobases and Nucleosides 6.4 Oligonucleotides 6.5 Amino Acids and Peptides 6.6 Proteins 6.7 Phospholipids 6.8 Conclusions Chapter 7. HILIC-MS for Targeted Metabolomics and Small Molecule Bioanalysis 7.1 Introduction 7.2 The role of HILIC-MS in targeted metabolomics versus other LC modes 7.3 Strategies for method development based on retention behavior of targeted metabolites on HILIC stationary phases 7.3.1 Retention behavior of metabolites on HILIC stationary phases 7.3.2 Robustness, mobile phase compositions, and matrix effects 7.4 Summary Chapter 8. HILIC for Food, Environmental, and Other Applications 8.1 Introduction 8.2 Food applications for HILIC 8.2.1 Review of HILIC analytical methods for food analysis 8.2.1.1 Sample preparation in HILIC methods applied to food matrices 8.2.1.2 HILIC methods applied to food matrices: chromatographic parameters and detection 8.2.2 Selected detailed examples of HILIC applications in food analysis 8.2.2.1 Melamine (MEL) and cyanuric acid (CYA) 8.2.2.2 Water soluble vitamins 8.2.2.3 Seafood and other toxins 8.3 Environmental and other applications of HILIC 8.3.1 Review of environmental applications based on the stages of method development 8.3.2 Selected detailed examples of environmental and other HILIC applications 8.3.2.1 Metals and their related organic compounds 8.3.2.2 Pharmaceutical compounds in aqueous environmental samples 8.3.2.3 Other applications 8.4 Conclusions Chapter 9. Theory and Practice of Two-Dimensional Liquid Chromatography Separations Involving the HILIC Mode of Separation 9.1 Fundamentals of multi-dimensional liquid chromatography 9.1.1 Scope 9.1.2 Potential advantages of two-dimensional separations over conventional separations 9.1.3 Modes of 2D separation 9.1.3.1 Offline fraction transfer 9.1.3.2 Online fraction transfer 9.1.3.3 Conceptual comparison of different 2D separation modes 9.1.4 Undersampling 9.1.5 Orthogonality 9.2 Complementarity of HILIC selectivity to other separation modes 9.3 Instrumentation and Experimental Considerations 9.3.1 Online versus offline 2DLC 9.3.1.1 Offline 2DLC 9.3.1.2 Online 2DLC 9.3.2 Dealing with solvent incompatibility 9.3.2.1 Partial mobile phase evaporation 9.3.2.2 Consideration of fraction transfer volume relative to the second dimension column volume 9.3.2.3 On-column focusing 9.3.3 Fast Separations 9.3.3.1 General considerations for fast LC separations 9.3.3.2 Fast HILIC separations 9.4 Applications 9.5 The future of HILIC separations in 2DLC.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Hydrophilic interaction liquid chromatography; Electronic books